Independent work of students as an integral part of the educational process in extracurricular times - E. Bondar (Academy of Cognitive and Natural Sciences, 2009)
Independent work of students always played an important role in preparation of specialists, but especially it grew in postsovetskoe time, becoming basis of studies in Institute of higher. Reformation of the system of higher education puls before it new problems, and also search of ways of their overcoming.